2000
DOI: 10.1002/(sici)1097-0223(200001)20:1<76::aid-pd752>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of mosaicism for a del(22)(q13)

Abstract: A case of prenatally detected mosaicism for a del(22)(q13) is reported. CVS was performed because of abnormal fetal ultrasound findings: cystic 'tumour' in the fetal neck and the upper thoracic aperture. Karyotypes from chorionic villi were suspicious of an aberration concerning the long arm of one chromosome 22. FISH analysis demonstrated mosaicism for a distal 22q deletion in fetal fibroblasts. The deletion was postnatally confirmed by FISH with a chromosome-specific 22q probe. The 'tumour' on autopsy turned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Somatic mosaicism for structural chromosome abnormalities is a well-recognized but rarely reported phenomenon and has been described for a number of syndromes, including 22q13 deletion (Riegel et al 2000;Phelan et al 2001), neurofibromatosis type 1 (Ainsworth et al 1997;Tinschert et al 2000), 22q11.3 deletion (Kasprzak et al 1998), dystrophin (Bunyan et al 1995), 1p36.33 deletion (Eugster et al 1997), Angelman syndrome 15q11-13 deletion (Tekin et al 2000), and 19q13.33 deletion (Mikelsaar et al 2001). Molecular confirmations of germline mosaicisms for deletions of 22q11.2 (Hatchwell et al 1998) and Williams-Beuren syndrome (Kara-Mostefa et al 1999) have also been reported.…”
Section: Mosaicism For Cryptic Deletion In Two Patients With the Anirmentioning
confidence: 99%
“…Somatic mosaicism for structural chromosome abnormalities is a well-recognized but rarely reported phenomenon and has been described for a number of syndromes, including 22q13 deletion (Riegel et al 2000;Phelan et al 2001), neurofibromatosis type 1 (Ainsworth et al 1997;Tinschert et al 2000), 22q11.3 deletion (Kasprzak et al 1998), dystrophin (Bunyan et al 1995), 1p36.33 deletion (Eugster et al 1997), Angelman syndrome 15q11-13 deletion (Tekin et al 2000), and 19q13.33 deletion (Mikelsaar et al 2001). Molecular confirmations of germline mosaicisms for deletions of 22q11.2 (Hatchwell et al 1998) and Williams-Beuren syndrome (Kara-Mostefa et al 1999) have also been reported.…”
Section: Mosaicism For Cryptic Deletion In Two Patients With the Anirmentioning
confidence: 99%
“…Despite a lack of phenotypic similarity to VCFS/DGS, a number of microdeletions were identified fortuitously by the absence of signal from the 22q13 control probe from commercially available VCFS/DGS fluorescence in situ hybridisation (FISH) probe kits. [5][6][7][8] A percentage of 22q13 deletions are the result of unbalanced translocations and therefore their phenotype is complicated by the presence of duplicated material from a second chromosome (8/37 patients 4 ). Deletions of 22q13 are also associated with ring chromosome 22,9 which is usually complicated by mosaicism of the r (22).…”
mentioning
confidence: 99%
“…Apart from patients with r(22) chromosomes,14-17 mosaicism for del(22)(q13) has so far been described in a 5.5-year-old girl with global developmental delay, epilepsy, and mild facial dysmorphisms,18 and in two fetuses it was prenatally diagnosed because of ultrasound anomalies19 and increased risk of Down’s syndrome determined by maternal serum screening 4. To the best of our knowledge, Case 1 represents the first patient with 22q13.3 deletion syndrome associated with a complex mosaic chromosome rearrangement consisting of a 22q13.2-qter chromosome deletion in 45% of her cells, and an apparently normal cell line that actually carries a 22q13 segmental paternal UPD in 55% of the cells.…”
Section: Discussionmentioning
confidence: 97%